Effect of nano selenium or nano silicon on antioxidants activity and leaf anatomy of lavender plant under salinity stress conditions - Ahmed, Aya G.; M. Khalil, Mahmoud; M. Ebrahim, Darwish; Sh. Gendy, Ahmed; G.El-Banna, Sabah; S.Boghdady , Mohamed (Journal of Neonatal Surgery, 2024)
This study was conducted at the Nursery of ornamental plants, Hort. Depart., Faculty of agricultural., Zagazig Univ., and at Hormmone Laboratory, Department of Environmental Studies, Institute of Graduate Studies & Research- Alexandria University Egypt, during two consecutive seasons of 2023 and 2024 to evaluate the effect of foliar application of biological selenium and silicon nanoparticles under water salinity conditions on antioxidants activity and leaf anatomy of lavender plant. The tested saline water was at four levels (control(157), 1000, 1500, 2000 ppm ). While, examined foliar spraying with nano-particles were seven concentrations viz, (control, 100, 200 and 300 ppm) nano- selenium and (100, 200 and 300 ppm) nano- silicon . The achieved results of this study showed that the foliar spray with nano-selenium or nano- silicon decreased thiobarbituric acid reactive substances and DNA breakages (%), plants sprayed with 300 ppm nano- selenium or 300 ppm nano-silicon increased amount of catalase activity in leaves. Plants treated with nano- selenium at level 200 ppm induced a prominent increase in medvein and lamina thickness by 15.8 and 8.4 % respectively compared to control (14.4, 16.7%). Plants treated with silicon at level 200 ppm increased medvein thickness by 14.3 %, while lamina thickness decreased by 17.7%..